Successful design and delivery of a professional poster. Issue 8 (28th June 2017) - Berg, Judith; Hicks, Rod
Abstract: Background and purpose: Poster presentations are increasingly popular for dissemination of scientific and clinical knowledge at professional meetings; however, this professional skill is generally absent from advanced practice registered nurse (APRN) curricula and acquisition of the skill must occur in other arenas. The purpose of this article is to promote professional development by educating APRNs, students, and faculty on the essentials of poster development and presentation. Methods: To aid in poster presentation skill development, types of posters, advantages and disadvantages, content and design, and tips to enhance these presentations are discussed. What is known on these topics is summarized and emphasis on professional appearance and conduct is highlighted. Conclusions: Content and layout, use of color, imagery, and positive and negative space are crucial design elements. Poster presentation essentials include being prepared, professional appearance, and professional behavior. Implications for practice: Designing and presenting a professional poster is an essential skill for all APRNs as the ability to communicate knowledge is central to the role.